KAMPANYE ANTI KEKERASAN SEKSUAL TERHADAP PEREMPUAN DAN ANAK DI UNIVERSITAS NEGERI GORONTALO - Cinta Labaso; Sulastri Gala; Cicin Nune (Journal of Community Services on Multidisciplinary Sciences, 2025)
Sexual violence against women and children is a systemic issue that creates gender inequality and long-term trauma, including within higher education institutions such as Gorontalo State University. This campaign was designed as part of a community service initiative using a quantitative approach through literature studies and documentation of actual cases. The goal of this activity is to raise awareness among the academic community and to build an internal protection system based on visual education and written information. Findings show that educational media such as videos and brochures can play a significant role in fostering collective awareness of sexual violence issues. These results reinforce the argument that media- and legal-literacy-based campaigns are a relevant preventive alternative.